Storage of cereal seeds at 4 °C - Zadorozhna, Olha; Shyianova, Tetiana (Problems of Cryobiology and Cryomedicine, 2026)
Seed longevity was studied for wheat (Triticum aestivum): var. еrythrospermum, var. lutescens spring and winter bread; spring durum wheat (Triticum durum): var. hordeiforme, var. leucurum, var. melanopus, var. alexandrinum; winter rye (Secale cereale) subsp. cereale var. vulgare; spring barley (Hordeum vulgare): var. nutans, var. erectum, var. rikotense, var. nudum, var. pallidum; maize (Zea mays) subspecies: popcorn (subsp. everta), flint corn (subsp. indurata), dent corn (subsp. indentata), semident corn (subsp. semidentata), sweet (subsp. saccharata) when stored at a temperature 4ºC and seed moisture content of 6-7%. We assessed the germination dynamics of 41 samples of these genotypes during storage for up to 10 years. For most samples, no significant differences in germination were found as compared to the initial one. In some cases, an increase in seed germination was observed after 4–8 years of storage. Variations in seed germination depending on sample genotype were tracked. The paper analyses differences in seed longevity of different cultivars of studied species and discusses the effect of low temperatures on seed longevity and expression of genes, especially those that enhance abscisic acid catabolism. Probl Cryobiol Cryomed. 2025; 35(3): 149—156